Chemical composition and biological activities of essential oils from Goniothalamus and Xylopia (annonaceae) species - Abdul Ghani, Siti Humeirah (2012)
The use of plant essential oil in daily care products, cosmetics and fragrances has increasingly gained attention in recent years. However, detailed studies on the oil especially in the aspects of chemical compositions, biological activity, safety and efficacy as a raw material for daily care products are limited thus limiting its commercial potential. The essential oils of five plant species from the family Annonaceae, namely Goniothalanus macrophyllus, G. tortilipetalus, Xylopia malayana, X. fusca and X. elliptica were studied and their chemical compositions were analyzed by Gas Chromatography (GC) and Gas Chromatography/Mass Spectrometry (GC/MS). The leaf oil from X. malayana (1.39%) which was obtained from a water distillation produced the highest yield of essential oil. The chemical compositions of the essential oils from both species were analyzed by comparing their Retention Indices (RI) with the literature values, by comparing their mass spectral data with the mass spectral database from the published or by co-chromatography with authentic samples. This is the first report on the chemical compositions, antimicrobial activities and cytotoxicity effects of the essential oils from G. tortilipetalus, X. fusca and X. elliptica. The chemical constituents of the oils differed from species to species but were mainly of monoterpenoids and sesquiterpenoids. A total of 239 components were identified, representing 42.5% to 91.6% of the total oils. The main monoterpenoids were α-pinene, linalool, terpinen-4-ol,1,8-cineole and α-terpineol while geranyl acetate, geraniol, bicyclogermacrene and spathulenol are the major sesquiterpenoids identified from the oils. The essential oils together with eight standards: α-pinene, linalool, geraniol, geranyl acetate, terpinen-4-ol, limonene, 1,8-cineole and β-pinene were evaluated for their antimicrobial properties against nine microorganisms including Gram positive and Gram negative bacteria, and yeast by using the broth microdilution method. The essential oils exhibited antimicrobial activities (MIC values between 156-2500 μg/ml) against all of the microorganisms tested, except for Pseudomonas aeruginosa and Escherichia coli. The standards tested exhibited weak antimicrobial activities (MIC values >5000 μg/ml) against all of the microorganisms tested except for α-pinene. The cytotoxicity of the oils was evaluated against the human normal Chang liver and human normal skin fibroblast cell lines. The essential oils from the twig of X. elliptica and the leaf of G. tortilipetalus were found to be non-cytotoxic towards the Chang liver cell line even at higher concentrations (IC50 >1000 μg/ml). The other oils, however, exhibited moderate to weakly cytotoxic activity against both cell lines with the IC50 values ranged from 97.7 μg/ml to 877.0 μg/ml. The study revealed the potential use of the essential oils from ariel parts of Xylopia and Goniothalamus species as a new ingredient for various practical applications.